Calculation of the driving rain wall factor using ray tracing. Issue 179 (August 2018) - Tsoka, Stella; Thiis, Thomas K.
Abstract: The current study presents a simplified method towards the improvement of the ISO Standard for the wind driven rain (WDR) assessment; given that the corresponding semi-empirical ISO model only provides wall factor values for a limited number of façade configurations, potential variations along the building façades such as protrusion of windowsills, extrusions or roof overhangs are only partially accounted for and as a result, significant overestimations of driving rain impingement at the respective spots, located in the 'rain shadow' may occur. In order to encounter this limitation for areas in the rain shadow, the present study proposes the use of the ray tracing method so as generate a building specific wall factor at a significantly low computational cost. Both validation and application results showed that the method can capture the distinct effect of the overhang and the windowsills in terms of rain sheltering while on the other hand, dynamic characteristics of the wind and more complex phenomena cannot be handled. Highlights: A method towards the improvement of the ISO Standard for WDR assessment is proposed. Ray tracing is used for the wall factor calculation. Small scale details along the façade are henceforward accounted. Dynamic characteristics of the wind cannot be handled by the method. ISO model is improved for areas on rain sheltering at low computational cost.